2001
DOI: 10.1111/j.1532-849x.2001.00026.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comparison of the fracture resistance and failure mode of fiber, ceramic, and conventional post systems at various stages of restoration

Abstract: The fiber posts evaluated provided an advantage over a conventional post that showed a higher number of irretrievable post and unrestorable root fractures. At the stage of final restoration insertion, there was no difference in force to failure for all but the FibreKor material, which continued to be weaker than all other tested materials. The fiber posts were readily retrievable after failure, whereas the remaining post systems tested were nonretrievable. J Prosthodont 2001;10:26-36.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
149
3
12

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(175 citation statements)
references
References 19 publications
11
149
3
12
Order By: Relevance
“…4 With a modulus of elasticity similar to dentin, the fibre post can reduce the concentration of stress and thus the rate of catastrophic root fracture compared with cast posts. 5 Non-metal posts can be used when coronal dentin remains and the crown is well supported by the remaining tooth structure. A small percentage of the population is hypersensitive to dental alloys containing noble and base metals, such as palladium and nickel.…”
Section: Discussionmentioning
confidence: 99%
“…4 With a modulus of elasticity similar to dentin, the fibre post can reduce the concentration of stress and thus the rate of catastrophic root fracture compared with cast posts. 5 Non-metal posts can be used when coronal dentin remains and the crown is well supported by the remaining tooth structure. A small percentage of the population is hypersensitive to dental alloys containing noble and base metals, such as palladium and nickel.…”
Section: Discussionmentioning
confidence: 99%
“…30,32,33 With respect to mechanical failures stemming from separation between the post and core, there were no such reported cases. It has been suggested that the tensile bond strength between cores and posts is strongly dependant on the confi guration of the post head.…”
Section: Discussionmentioning
confidence: 99%
“…It is the most commonly used technique in the studies evaluating the fracture resistance of postrestored teeth [29,30]. Therefore, its use facilitates comparison with other studies.…”
Section: Discussionmentioning
confidence: 99%